Clasificaciones y subclases del pronombre en los tratados gramaticales del siglo XVI - Maquieira Rodríguez, Marina A. (Estudios humanísticos. Filología, 1990)
Not all the treatises on grammar written throughout the 16th century consider the pronoun as an independent part of the sentence; some, in fact, regard it as a nominal sub-class.The authors of the period, unanimously, tend to characterize it as a substitute for the noun according to a sintactic-distributional criterion, semantic-based, at times pointing at some formal feature person or declension or referring to its deictical capacity. Similarly, when dealing with the pronoun, these grammarians establish classifications, as it was usual with the remainder word-classes, yet not always according to the same point of view. It has been my aim in this paper to check such classifications, as well as examine the different subclasses steming from them.Those authors propose schemata of three, and one classification, whose root is in some cases formal, in some significative, being not unusual that the same grammarians combine in their proposals both.On the other hand, there are not many specific characterizations of pronominal subclasses, as is the case with the class itself, although it is true that some, like the personal or possessive ones, receieve an attention far more detailed than the rest.